Cloning, characterization, and physical mapping of the canine Prop-1 gene (PROP 1): exclusion as a candidate for combined pituitary hormone deficiency in German shepherd dogs - LANTINGA-VAN LEEUWEN, I. S; KOOISTRA, H. S; MOL, J. A; RENIER, C; BREEN, M; VAN OOST, B. A (Cytogenetic and genome research, 2000)
Abnormalities in the genes encoding Pit-1 and Prop-1 have been reported to cause combined pituitary hormone deficiency (CPHD) in mice and humans. In dogs, a similar phenotype has been described in the German shepherd breed. We have previously reported that the Pit-1 gene (POU1F1) is not mutated in affected German shepherd dogs. In this study, we report the isolation and mapping of the canine Prop-1 gene (PROP1), and we assessed the involvement of PROP1 in German shepherd dog dwarfism. The canine PROP1 gene was found to contain three exons, encoding a 226 amino acid protein. The deduced amino acid sequence was 79% and 84% homologous with the mouse and human Prop-1 protein, respectively. Using fluorescence in situ hybridization, PROP1 was mapped to canine chromosome 11. Further mapping with a canine radiation hybrid panel showed co-localization with the polymorphic DNA marker AHT137. Sequence analysis of genomic DNA from dwarf German shepherd dogs revealed no alterations in the PROP1 gene. Moreover, linkage analysis of AHT137 revealed no co-segregation between the PROP1 locus and the CPHD phenotype, excluding this gene as candidate for canine CPHD and providing a new spontaneous model of hypopituitarism.